Dielectrical Properties of a Novel Porcelain Produced from Natural Clay, Waste Glass and Fly Ash - (:unkn) unknown (WALTER DE GRUYTER GMBH, 2009)
A novel porcelain was obtained by sintering 50% kaolinite clay, 25% waste glass and 25% fly ash (a by-product of Turkey thermal power plant) at different temperatures of 1373-1523 K (1100-1250 degrees C). The microstructure and phase changes on heating were studied using SEM and XRD techniques. Fly ash used in this Study contributed towards development of anorthite (CaO center dot Al2O3 center dot 2SiO(2)) phase by crystallization of melted glassy phase. In samples exposed to sintering for 5 hours in 1523 K, viscosity and porosity in the structure decreased when the glassy phase melted. Dielectric permittivity (real and imaginary), conductivity and tan delta as a function of temperature were analyzed at 10 KHz frequency. Samples exposed to sintering for 5 flours exhibit increased conductivity in the 200-260 degrees C temperature range. This observation corresponds to the settlement of changeable cations in more stable octahedral sites during sintering. These results are significant in terms Of usability of waste materials like waste glass and fly ash in obtaining new generation materials and in electric-electronic industry.
Keywords: Porcelain; Waste glass; Fly ash; Dielectric properties; ELECTRICAL-CONDUCTIVITY; BEHAVIOR; SUBSTITUTION; RESISTIVITY; FELDSPAR; QUARTZ